(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
Today, the number of speakers of the American or British accent of the English language is growing. Therefore, it is natural for people to be interested in the history of these accents. The article also analyzes the history of the origin of British and American accents in English, the stages of their development, and their phonetic aspects and differences. Moreover, it highlights the process of origin of the standard pronunciation of Received Pronunciation (RP) formed in the territory of the United Kingdom and the general American pronunciation developed in the United States, and analyzes the main differences between British and American accents, such as sound pronunciation, intonation, intonation, and stress.